Leveraging networks to enhance sustainability: a rhizomatic approach for designer fashion enterprises - Annabel Robinson; Paul Langley (Sustainability: Science, Practice, & Policy, 2025)
The fashion industry is the second most polluting industry in the world today, and in the industry, small- and medium-sized enterprises (SMEs) and micro-businesses significantly outnumber large fashion brands. Designer fashion enterprises (DFEs) are micro-businesses that produce designer fashion and they are typically embedded in collaborative networks to survive and grow. This article provides insights into how these networks can be leveraged for sustainability. We conducted interviews with ten DFEs in London and our analyses of the data identified that these firms come up against a range of sustainability challenges. Our study of these networks reveals that the businesses do not rely on other designers due to the competitive nature of the industry, despite facing the same barriers to sustainability. “Rhizomatic theory” is a post-structuralist concept that challenges hierarchical models of knowledge flows. Rhizomatic structures lend themselves to emerging fields like sustainable fashion as they are ever-evolving, constantly producing, and negotiating information. A rhizomatic approach could leverage DFEs’ networks and assist them to achieve greater sustainability threefold – self-identifying as “sustainable,” normalizing designer-to-designer connections, and increasing the open negotiation of sustainability knowledge. We contribute to theory on DFE networking and its application to help practitioners increase sustainability across the industry.